From sadness to anger: Public perception over Covid-19 news coverage in Indonesia - Sita Winiawati Dewi; Albertus Magnus Prestianta; Utami Diah Kusumawati (Universitas Bunda Mulia, 2022)
The Covid-19 pandemic has driven up news media consumption worldwide. However, the concomitant rise of misinformation and disinformation has disrupted the dissemination of verified information, particularly in the digital media. The role of the press has been challenged. This research aims to measure the public perception of Covid-19 reporting in Indonesia and how the public responds to the news. This research processes data using text analysis and cross-tabulation to understand the pattern and correlation between variables. Most respondents agree that the media has done a good job in reporting on Covid-19 and distributing the information to the public, with few leaning towards a more neutral tone. However, social media ranks first as the most popular platform to search for Covid-19-related information, followed by online media and television. Despite the generally positive assessment over the role of media and the quality of Covid-19 reporting during the pandemic, most respondents limit the amount of time they spend on and the quantity of Covid-19-related news they consume as they experience sadness, loneliness, and disappointment.